PENINGKATAN KOMPETENSI TEKNIS DAN LINTAS BUDAYA MELALUI PROGRAM PERTUKARAN PELAJAR INTERNASIONAL DI WUHAN VOCATIONAL COLLEGE OF SOFTWARE AND ENGINEERING, CHINA - azhar, Haniyyah Azhar; Wahyudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The MBKM International Student Exchange program is one implementation of Indonesia's Merdeka Belajar Kampus Merdeka (MBKM) policy, providing students with the opportunity to gain learning experiences at overseas partner institutions. This study reports on the participation of a student from Universitas Singaperbangsa Karawang in an international student exchange program at Wuhan Vocational College of Software and Engineering (WHVCSE), Wuhan, China, from March 26, 2026. The program aimed to enhance academic and technical competencies, develop intercultural communication skills, and expand international academic networks. During the program, the participant engaged in courses covering Programmable Logic Controller (PLC), Data Communication Technology, Mechanical Operation Robot, Engineering Computer Graphics, Digital Factory Virtual Simulation, Automotive Wheel Hub Automated Assembly Line, Fundamentals of Automatic Control, Industrial Chinese, Physical Education, and cultural development activities. The results demonstrate that the program made meaningful contributions to technical competency enhancement, intercultural character development, and professional readiness for global industrial challenges.